2001
DOI: 10.1117/1.1383780
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of multiple green fluorescent protein color variants and dyes using two-photon microscopy and imaging spectroscopy

Abstract: Abstract. The imaging of living cells and tissues using laser-scanning microscopy is offering dramatic insights into the spatial and temporal controls of biological processes. The availability of genetically encoded labels such as green fluorescent protein (GFP) offers unique opportunities by which to trace cell movements, cell signaling or gene expression dynamically in developing embryos. Two-photon laser scanning microscopy (TPLSM) is ideally suited to imaging cells in vivo due to its deeper tissue penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 15 publications
0
137
0
Order By: Relevance
“…Biogenetic evidence demonstrated that the GR (Umesono and Evans, 1989) and the MR (Govindan et al, 1991) form homodimers through a dimer interface within their zinc finger regions (ZFRs), and these receptors share complete sequence identity in this ZFR dimer interface, suggesting that this region might mediate heterodimerization as well (Liu et al, 1995). To look for such an interaction in a spatiotemporal-specific manner, we conducted a FRET analysis coupled with a new technique called spectral imaging fluorescence microscopy (Lansford et al, 2001;Hiraoka et al, 2002) to compensate for varying levels of protein expression. This technique allowed us to detect spectral changes in fluorescence in living cells and to address several controversial points of intermolecular FRET (Miyawaki and Tsien, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Biogenetic evidence demonstrated that the GR (Umesono and Evans, 1989) and the MR (Govindan et al, 1991) form homodimers through a dimer interface within their zinc finger regions (ZFRs), and these receptors share complete sequence identity in this ZFR dimer interface, suggesting that this region might mediate heterodimerization as well (Liu et al, 1995). To look for such an interaction in a spatiotemporal-specific manner, we conducted a FRET analysis coupled with a new technique called spectral imaging fluorescence microscopy (Lansford et al, 2001;Hiraoka et al, 2002) to compensate for varying levels of protein expression. This technique allowed us to detect spectral changes in fluorescence in living cells and to address several controversial points of intermolecular FRET (Miyawaki and Tsien, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The results illustrated in Figure 5 and Table 1 show that, while each spectral mapping algorithm gave slightly different results, results were spatially and statistically similar, suggesting that spectral identification algorithms other than the previously used supervised classification (8,9) and LSU (3,4,(8)(9)(10)(11) will have utility for spectral microscopy. Moreover, these results showed that a full range of algorithms could be used to derive similar results, providing the analyst with a host of options for solving any particular spectral analysis problem.…”
Section: Discussionmentioning
confidence: 86%
“…The most widely used methods include both supervised classification techniques (8,9) and linear spectral unmixing (LSU) (3,4,(8)(9)(10)(11). All of these studies demonstrated success utilizing these techniques with spectral microscopy data.…”
Section: Society For Analytical Cytologymentioning
confidence: 99%
“…Last, several research groups have focused on building new tools for image rendering and analysis for biological data mining. Although this is a vast area of research, I have included references for a small sampling of papers and reviews to provide examples of ongoing research (Lansford et al, 2001;AlKofahi et al, 2002AlKofahi et al, , 2003Jacobs et al, 2003;Megason and Fraser, 2003;Herskovits et al, 2004;Huang and Murphy, 2004;Warner et al, 2004;Ledesma-Carbayo et al, 2005;Liebling et al, 2005;Lin et al, 2005;Peng et al, 2005;Suhling et al, 2005;Toga, 2005;Tyszka et al, 2005a;Forouhar et al, 2006;Luders et al, 2006).…”
Section: Tools For Image Analysismentioning
confidence: 99%